Vulnerability of Irrigated Agriculture to a Drier Future in New Mexico᾿s Mesilla and Rincon Valleys - Granados-Olivas, Alfredo (UACH, 2022)
Abstract Agriculture depends on irrigation in many regions, especially in arid and semi-arid areas. Climate variability and prolonged droughts in water-scarce regions further limit water availability, posing dire water sustainability concerns. The challenge is particularly grave in regions like New Mexico’s Mesilla and Rincon Valleys where water resources are increasingly strained due to growing water demand in domestic, industrial, and agricultural sectors. Understanding the vulnerability of irrigated agriculture to future climate conditions helps water authorities and farmers to better plan for future crop production.